Making sense of innovation management - Kettunen, Jari.; Ilomäki, Sanna-Kaisa.; Kalliokoski, Petri; Teknologiateollisuus; Teknologiainfo Teknova (Helsinki : Teknologiainfo Teknova, 2008)
This book provides an overview of the broad field of innovation management. The innovation management is approached from three major viewpoints: 1) strategies and business models 2) steering and funding mechanisms 3) networking, capabilities and incentives. There are numerous case examples that illustrate the referenced theories and models.
S. 222-227: Glossary
Teknologiateollisuuden julkaisuja 12/2007.
Julkaistu myös verkkoaineistona.
Keywords: Business; Product management; Management; Technological innovations -- Management; Entrepreneurship; Leadership; liiketoiminta; innovaatiot; johtaminen; liiketoimintamallit; tutkimus- ja kehittämistoiminta; tuotekehitys; yritysstrategiat; ohjausjärjestelmät; rahoitus; verkostoituminen; kannustimet; liikkeenjohto; kehittäminen; mallit (mallintaminen); strategiat; strateginen johtaminen; strateginen suunnittelu; yritystoiminta; affärsverksamhet; affärsverksamhetsmodeller; forskning och utveckling; produktutveckling; företagsstrategier; styrsystem; finansiering; nätverksbyggande; incitament; företagsledning; utveckling (verksamhet); modeller (alster); strategier; strategisk ledning; strategisk planering; företagsverksamhet; innovationer; ledarskap (verksamhetsledning); development; innovation; management; funding; networking; business models; control systems; business strategies; innovation management; strategies